The Precariat: the new dangerous class - Fogues, Aurora (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
Recensión de: Standing, G. (2011). The Precariat: the new dangerous class. London: Bloomsbury, 198 pp.